FAKTOR PENYEBAB TIDAK TERCAPAINYA SASARAN MUTU RELOKASI KONTAINER JALUR MERAH (BEHANDLE) DI PT. MUSTIKA ALAM LESTARI.docx - Fani Nur Fadilah; Winoto Hadi (Universitas Negeri Jakarta, 2018)
PT. Mustika Alam Lestari is a company engaged in port services, as well as serving physical inspection of behandles. In this activity, there is a relocation of behandle containers, which is the time required for goods owners to move containers from the import field to the behandle field. This activity starts after printing. behandle card.The author took this topic because the relocation of behandle containers often did not meet the set time standards. Because there are several factors that cause these activities do not meet quality objectives. The method used in the preparation of this final task is the interview method, as well as the search of several data sources, it can be concluded why import container relocation activities often do not meet the quality target which is due to the lack of available tools in the field. Therefore, the author tries to analyze this and try to provide input by adding the tools that are in the field so that the target stipulated quality can be in accordance with the target.